Integration of Geogebra and Desmos in analytical geometry learning: Its effect on students' mathematical reflective thinking - Oktafia, Mesi; Erita, Selvia (Universitas Riau Kepulauan, 2025)
This study aims to examine the effect of integrating GeoGebra and Desmos in Analytic Geometry learning on students’ mathematical reflective thinking ability. Both software applications were implemented simultaneously within a single instructional scenario, complementing each other in facilitating visualization, exploration, and conceptual reflection in analytic geometry. The study employed a quantitative approach using an experimental method with a Randomized Control Group Only Design. The research participants consisted of 27 third-semester students from the Mathematics Education (Tadris Matematika) Program at IAIN Kerinci, divided into an experimental group (III A, 14 students) and a control group (IIIB, 13 students). The experimental group received instruction in Analytic Geometry through the integrated use of GeoGebra and Desmos, whereas the control group was taught using conventional methods. The research instrument was an essay-type test that required mathematical reflective thinking. The instrument was validated through content and empirical validity testing, demonstrating high reliability with a Cronbach’s Alpha coefficient of 0.958. Data were analyzed using an independent samples t-test after meeting the assumptions of normality and homogeneity. The results showed that there was an effect of mathematical reflective thinking skills on students in the experimental class (sig. < 0.05). These findings confirm that the integrated use of GeoGebra and Desmos functions effectively as reflective cognitive tools in supporting the development of students’ mathematical reflective thinking ability in Analytic Geometry learning.